(untitled) (Research, Society and Development, 2022)
The Artificial Intelligence inserted in the educational sector provides the handicapped a differentiated learning, helping to increase the student’s engagement. This is because different technology resources are available at any time, such as gamification, which raise the student’s interest in education, this strategy turns students into protagonists with fundamental skills and more knowledge. With more and more inventions available online that are not only brought by the educator, Educational Intelligence is a good idea for students to learn from wherever they are. Besides stimulating learning, it is possible to create customized systems with each student’s profile. This research is based on bibliographic data, elaborated from published material, such as books, articles, periodicals and the Internet, and on qualitative data, since it aims at approaching the subjective aspects of social phenomena and human behavior, thus trying to approach themes that cannot be quantified in equations and statistics, with a methodological base of systemic paradigm, based on the complexity theory and having as a study object the artificial intelligences inserted in educational environments as learning promotion.